Changes in antioxidant pathway enzymes in Indian mustard leaves due to white rust infection - VEENA JAIN; A.S. RATHI, SAPNA*, SUNITA JAIN (Indian Phytopathology, 2009)
The activities of antioxidant pathway enzymes in leaves of white rust resistant (RH 781) and susceptible (Varuna) genotypes of Indian mustard (Brassica juncea L.) were estimated in uninoculated and inoculated leaves. The activities of peroxidase and superoxide dismutase were higher in healthy leaves of susceptible genotype than resistant genotype, while the activities of catalase, ascorbate peroxidase and glutathione reductase were higher in resistant genotype in comparision to susceptible one. Inoculation with Albugo candida pathogen on leaves resulted in significant enhanced activities of, catalase, ascorbate peroxidase and glutathione reductase in leaves of resistant genotype as compared to the susceptible genotype. Inoculation of leaves showed enhanced activity of peroxidase, superoxide dismutase in susceptible genotype, whereas, its activity declined in resistant genotype.